Foreign Aid in Nepal: Importance, Trends and Government Initiatives (Economic Journal of Nepal, 2017)
Economic growth and development are in the forefront of international relations and policy making. Developed countries such as the United States and international organizations such as the World Bank and the International Monetary Fund provide assistance that attempts to help the economic growth of developing countries. Foreign aid has been recognized as the most crucial factor in enhancing economic development in many countries. Foreign aid is crucial factor to achieve higher and sustainable economic growth and development of Nepal. However, aid must be linked with sustainable growth and poverty reduction. The objectives of the paper are to study the importance, trends and government initiatives of foreign aids in Nepal.